Bencana, Informasi dan Keterlibatan Media - Prajarto, Nunung (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
This article describes the role and involvement of media in reporting disaster. Media involvement in giving people information on disaster should based on human safety, security and dignity. This paper suggests that media report on pre, during and after a disaster should consider human values at the first priority.